∫ 0 1 x 2 + 1 ln ( x + 1 ) d x = a π ln b
The equation above holds true for some real numbers a and b . Determine the value of a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Is it lengthy. I = ∫ l n ( t a n ( θ ) + 1 ) d θ = ∫ l n ( t a n ( π / 4 − θ ) + 1 ) = π / 4 l n 2 − ∫ l n ( 1 + t a n θ ) .So 2 I = π / 4 l n 2
Log in to reply
No, I was referring to Juvin's solution. And yeah your approach is much better and I also wanted to show a new substitution method which is useful in some other types of problems.
Having a change in variables, let x = t a n θ .
Then, x 2 + 1 = s e c 2 θ and d x = s e c 2 d θ as well. In addition, a change in limits would give the new upper and lower limits as a r c t a n 1 = π / 4 and a r c t a n 0 = 0 , respectively. Denoting the value of the integral as I, the solution are as shown in the photo. The determination of a and b yields 8 and 2 , respectively, and at once, a + b = 1 0
PS. The question, and the corresponding solution, were all done in Microsoft Word. I do apologize for being unable to do the entire solution in LaTeX.
Similar solution but slightly simpler.
I = ∫ 0 1 x 2 + 1 ln ( x + 1 ) d x = ∫ 0 4 π ln ( tan θ + 1 ) d θ = 2 1 ∫ 0 4 π ln ( tan θ + 1 ) + ln ( tan ( π − θ ) + 1 ) d θ = 2 1 ∫ 0 4 π ln ( tan θ + 1 ) + ln ( tan θ + 1 1 − tan θ + 1 ) d θ = 2 1 ∫ 0 4 π ln ( tan θ + 1 ) + ln ( tan θ + 1 2 ) d θ = 2 1 ∫ 0 4 π ln ( tan θ + 1 ) + ln 2 − ln ( tan θ + 1 ) d θ = 2 1 ∫ 0 4 π ln 2 d θ = 8 π ln 2 Let x = tan θ ⟹ d x = ( tan 2 θ + 1 ) d θ Using ∫ a b f ( x ) d x = ∫ a b f ( a + b − x ) d x
⟹ a + b = 8 + 2 = 1 0 .
Problem Loading...
Note Loading...
Set Loading...
Trigonometric substitution is good but very lengthy. A quick alternative would be to substitute x = 1 + y 1 − y then the integral becomes very easy to solve.
The motivation behind the substitution is that by doing this substitution, we can ,by using properties of log, get the original integrand back.